A comprehensive study of oxidative stress in patients with chronic otitis media - Celik, Mustafa; Koyuncu, İsmail (ENT Updates, 2020)
Objective: The purpose of this research study was to evaluate dynamic thiol/disulphide homeostasis (TDH) as a novel oxidative stress marker in participants with noncholesteatomatous chronic otitis media (ncCOM) and cholesteatomatous chronic otitis media (cCOM), as well as to investigate lipid hydroperoxide (LOOH), total antioxidant status (TAS), total oxidant status (TOS) and oxidative stress index (OSI) markers and compare the results with a healthy control group. Methods: This research was carried out at Harran University Medical Faculty Ear-Nose-Throat Department, between April 2017 and April 2019. This was a prospective controlled trial study including 121 participants, 40 ncCOM, 39 cCOM and 42 healthy controls. Total thiol, native thiol, disulphide levels and LOOH, TAS, TOS levels were measured in plasma of all patients and healthy volunteers. Results: In our study, we found that total thiol, native thiol levels, native thiol/total thiol ratios and TAS levels were significantly lower in cCOM patients compared with the control group (p<0.01). Disulphide/native thiol, disulphide/total thiol ratios, LOOH, TOS and OSI levels were significantly increased in the cCOM group compared with the control group (p<0.01). Conclusion: Oxidative stress (OS) is believed to be one of the underlying reasons for COM pathogenesis. In this research, we analyzed dynamic TDH as a novel OS marker using a novel improved fully automatic colorimetric technique, along with other parameters. This study may shed light on understanding the underlying reasons for the pathogenesis of COM and identify potential targets for antioxidant drug treatment.